2016
DOI: 10.1371/journal.pone.0157671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of an Antimicrobial Stewardship Program on Reducing the Incidence Rate of Healthcare-Associated Clostridium difficile Infection: A Non-Randomized, Stepped Wedge, Single-Site, Observational Study

Abstract: BackgroundThe incidence rate of healthcare-associated Clostridium difficile infection (HA-CDI) is estimated at 1 in 100 patients. Antibiotic exposure is the most consistently reported risk factor for HA-CDI. Strategies to reduce the risk of HA-CDI have focused on reducing antibiotic utilization. Prospective audit and feedback is a commonly used antimicrobial stewardship intervention (ASi). The impact of this ASi on risk of HA-CDI is equivocal. This study examines the effectiveness of a prospective audit and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…[ 2 ] Its clinical manifestations range from asymptomatic carriage to severe forms of fulminant colitis and death. [ 3 , 4 ] There has been a dramatic worldwide increase in the incidence and severity of CDI over the past 2 decades, [ 1 ] despite the prevention programs implemented in many countries. [ 2 – 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Its clinical manifestations range from asymptomatic carriage to severe forms of fulminant colitis and death. [ 3 , 4 ] There has been a dramatic worldwide increase in the incidence and severity of CDI over the past 2 decades, [ 1 ] despite the prevention programs implemented in many countries. [ 2 – 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in terms of systemic infections, increased education regarding judicious antibiotic use by limiting overprescription of antibiotics, cycling between antibiotic classes, and using combination therapies has led to a decrease in antibiotic resistance in systemic infections. [19][20][21][22] The ARMOR study is the only nationwide evaluation of antibacterial susceptibility of common ocular pathogens in the US, and now includes almost 1,000 additional isolates beyond those included in the 2015 evaluation. 18 Although trends over the past 7 years show a small but significant decrease in S. aureus resistance to some antibiotic classes, and confirmed the previous finding of a decrease in resistance among CoNS to ciprofloxacin, some increases in resistance were also noted.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the prior prevalence estimate and ours (5.1%) may be driven by Tsiouris et al study period being concentrated during the CDI epidemic driven by the BI/NAP/027 strain, whereas our study included cases before and after the outbreak. Another possible explanation for the differences in prevalence could be an increasing emphasis on antibiotic stewardship during the later years of our study, which has been shown to decrease the risk of CDI [30]. Finally, C. dificile testing in postcolectomy patients was likely low during the earliest years of our study period due to decreased recognition of CDE as a clinical entity.…”
Section: Discussionmentioning
confidence: 94%